Estilos de aprendizaje en estudiantes de posgrado de una universidad particular - Álvarez Flores, David (2001)
The purpose of the research is to comprehend the learning styles of graduate students in a private university in Lima. The descriptive correlational study was based on a sample of 186 students of different master degree programs. Kolb´s Learning Style Inventory (LSI) was applied, as adapted by Escurra to our milieu. The results show a proportional distribution of the different learning styles, finding no statistical relation between the learning styles and the different master´s programs, sex and educational level.